An Innovative Analysis of Infant Burials from the Chalcolithic Site of Fazael 2, Israel - Eshed, Vered; Bar, Shay (2012)
In 2007, excavation at the Chalcolithic site of Fazael 2 in the Jordan Valley (the first quarter of the fourth millennium BCE) revealed two baby burials under the floor of a habitation structure. One burial, an intact jar, was found in situ in the north-western part of the room. The second burial, a fetus, was found in situ in a primary deposition below the south-eastern corner of the structure, without any container. Both burials were removed from their location without excavation. The jar was taken for a computer tomography scan in the laboratory of Philips R&D Center, Haifa, and the second burial was removed as a block to the Tel Aviv University laboratory. The latter was excavated with traditional archaeological/anthological methods. A comparison of the two methods — traditional excavation and the CT scan — was carried out. This paper focuses on the methods used, the data gathered and the first analysis results of the research.